Characteristics of Polled Bali Cattle and Potential for Development in South Sulawesi - Zulkharnaim, Zulkharnaim; Baba, Syahdar; Muhammad, Hatta; Hasman, Hasman; Baco, Sudirman; Hasbi, Hasbi (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
Some cattle breeds that have evolved hornless versions include indigenous cattle. This research aimed to identify phenotypic and morphometric traits in Polled Bali cattle (PBC) as the indigenous cattle, this research is important for breed characterization. This study involved 165 heads of PBC, which included 60 males and 105 females. The lack of horns in PBC causes the interaction of the poll gene (P) and the scur gene (Sc). The PBC coat color is mainly reddish-brown (>40%), with black color on the hoof (>90%), switch of the tail (>68%), eyelid (>100%), and muzzle (>96%), with reddish-brown color on the mouth lash (>82%), and white color on legs (>50%), and rump patch (>50%). PBC are mainly humpless (100%), small on the dewlap size (100%), a thick line on the dorsal (>48%), and poll in males (82.76%), in females (52.27%), and scurs in males (17.24%) in females (47.73%). Net Replacement Rate (NRR) values were 145% (male) and 140% (female) and indicated that South Sulawesi Province was still capable of producing seed stock per year.